2011
DOI: 10.1055/s-0030-1260582
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Stabilized o-Quinone Methides, Thioquinones, and Selenoquinones: Trapping Important Reactive Intermediates and Beyond

Abstract: Quinone methides (quinomethanes) act as important intermediates in organic syntheses, as well as in chemical and biological processes. However, examples of such isolated species are scarce owing to their high reactivity. Other important reactive intermediates are thio-and selenoquinones. However, unlike quinones, they are highly unstable and consequently do not exist in nature, hence their chemical and biological properties remain unknown. In this account, we describe the first isolation of the above important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Our group has shown that organometallic moieties such as Cp*M (Cp* = pentamethylcyclopentadienyl, M = Ru, Rh and Ir) can stabilize reactive intermediates by modifying their electronic properties . More recently we have reported the synthesis of organometallic π‐bonded quinones [Cp*M(η‐C 6 H 4 O 2 )] n (M = Ru, n = –1; M = Rh, Ir, n = 0) and their usage as organometallic ligands for the preparation of a unique type of supramolecular assemblies with useful luminescence properties .…”
Section: Introductionmentioning
confidence: 99%
“…Our group has shown that organometallic moieties such as Cp*M (Cp* = pentamethylcyclopentadienyl, M = Ru, Rh and Ir) can stabilize reactive intermediates by modifying their electronic properties . More recently we have reported the synthesis of organometallic π‐bonded quinones [Cp*M(η‐C 6 H 4 O 2 )] n (M = Ru, n = –1; M = Rh, Ir, n = 0) and their usage as organometallic ligands for the preparation of a unique type of supramolecular assemblies with useful luminescence properties .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interest on the development of methods for quinone methides synthesis has been increased in the recent years [14], although simple quinone methides, such as, those without substituents at the exocyclic methylene group, are unstable compounds. Because of that, many efforts have been focused on their stabilization, mainly form quinone methide coordination complexes with transition metals [15,16,17]. To the best of our knowledge, however, none of the peltogynoid quinone methides have yet been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] They usually behave as heterodienes in Diels-Alder [2 + 4] cycloadditions with olefins to provide chroman type structures. [5][6][7][8][9][10] The high reactivity of o-quinone methides is illustrated, whereby the spectroscopic characterization of the parent molecule C 7 H 6 O (1), generated in situ, occurs only at temperatures below -100 C. 2,11 In contrast, we reported some years ago the first example where this elusive molecule (1) can be stabilized and isolated as an iridium complex pR-[Cp*Ir(Z 4 -C 7 H 6 O)] (4a) and pS-[Cp*Ir(Z 4 -C 7 H 6 O)] (4a'). [12][13][14] In these compounds the o-quinone methide ligand is now p-coordinated to the metal center through the internal diene carbons.…”
Section: Introductionmentioning
confidence: 99%